Is levosimendan effective in paediatric heart failure and post-cardiac surgeries? - Angadi, Ullas (Oxford University Press, 2013)
A best evidence topic in cardiothoracic surgery was written according to a structured protocol. The question addressed was ‘do children with heart failure post-cardiac surgery undergoing treatment with levosimendan have an acceptable haemodynamic improvement?’ The use of levosimendan as a vasoactive drug is an accepted intervention for patients with altered haemodynamics post-cardiac surgeries. However, the role of levosimendan and its efficacy have been debated. Eleven relevant papers were identified, which represented the best evidence to answer the question. The author, journal, date, country of publication and relevant outcomes are tabulated. The 11 studies comprised 3 randomized trials, 2 of which compared levosimendan and milrinone. A single-centre randomized study that included 40 infants showed that cardiac output (CO) and cardiac index (CI) increased overtime in the levosimendan group compared with the milrinone group. The significant interaction for CO (P = 0.005) and CI (P = 0.007) indicated different time courses in the two groups. A similar, European randomized study undertaken on neonates (n = 63) showed better lactate levels [P = 0.015 (intensive care admission); P = 0.048 (after 6 h) with low inotropic scores in the levosimendan group. Although the length of mechanical ventilation and mortality were less, this was statistically insignificant. A retrospective cohort analysis (n = 13) in children reported a reduced use of dobutamine and improvement in the ejection fraction from 29.8 to 40.5% (P = 0.015) with the use of levosimendan. In a questionnaire-based study from Finland, 61.1% of respondents felt that it had saved the lives of some children when the other treatments had failed. No study reported any adverse effect attributable to use of levosimendan. In conclusion, the above studies were in favour of levosimendan as a safe and feasible drug providing potential clinical benefit in low cardiac output syndrome (LCOS) and post-cardiac surgeries when other vasoactive drugs were insufficient to maintain stable haemodynamics. A small sample size was indeed a limitation in all the above studies. Furthermore, it is best used as a rescue drug on a named-patient basis. A small sample size was indeed a limitation in all the above studies. Larger, well-designed trials are required to further evaluate the efficacy and feasibility of levosimendan in paediatric heart failure and post-cardiac surgeries.